PERANCANGAN SISTEM BERBASIS WEB MENGGUNAKAN METODE SCRUM PADA BUMDES (BADAN USAHA MILIK DESA) DI DESA KEDUNGBANTENG - Zaqi, Ahmad Zaqi Azkal Azkiak; Sartika Wiguna, Anggri; Santoso, Heri (Fakultas Sains dan Teknologi, 2023)
This research is oriented towards designing a web-based system for Bumdes (Village Owned Enterprises) in Kedungbanteng Village using the scrum approach method. The design process using the scrum method is implemented through the sprint stages in a 30-day sprint time cycle. System design using scrum is one method that is widely used in system design that relies on team collaboration. Intceremental project or product, and the iteration process to realize the end result of the system. The purpose of this research is to design a web-based system as an answer to the research results and the problems found in the research object, one of which is the need for the application of science and technology (Science and Technology) so that it can facilitate and support the effectiveness of the research object, this is Bumdes (Village-Owned Enterprise) in Kedung Banteng Village, using the scrum method with system design showing that scrum is an appropriate and relevant method used in carrying out the project (system) design process on a long-term scale and is carried out from (start on ziro) because the design using this method is process oriented and commitment the team in achieving the main mission, namely system design through the stages of the method (planning, sprint, and evaluation) and this method is highly recommended for beginners who are involved in the world of informatics.